Evaluation of a grandparent bereavement support group in a Pediatric Palliative Care Hospice. (4th March 2022) - Arnone, Madelena; Dumond, Lynn Grandmaison; Yazdani, Nahal; El-Baroudi, Rayan; Pouliot, Annie; Modanloo, Shokoufeh
Abstract: This study aimed to explore grandparents' experiences of grief after the death of a grandchild, their perception of socially supportive behavior as well as their satisfaction with a bereavement support care. A six-session bereavement support group was implemented, followed by a cross-sectional survey with open-ended questions. The death happened mostly in the last 2 years (26, 90%). The findings revealed the presence of grief (mean score of 67, SD 13) and existing perception of socially supportive behaviors (mean score of 79, SD 23) after participation in the bereavement group. The thematic analysis showed three themes of 'We are feeling it; There are ways to heal and return to a different normal; We want to help our family'. This study adds to the existing literature about the experience of grandparents coping with grief, explores some of their challenges, and needs after the death of a grandchild.